Attribution of Space‐Time Variability in Global‐Ocean Dissolved Inorganic Carbon - Carroll, Dustin; Menemenlis, Dimitris; Dutkiewicz, Stephanie; Lauderdale, Jonathan M.; Adkins, Jess F.; Bowman, Kevin W.; Brix, Holger; Fenty, Ian; Gierach, Michelle M.; Hill, Chris; Jahn, Oliver; Landschützer, Peter; et al. (Global biogeochemical cycles, 2022)
The inventory and variability of oceanic dissolved inorganic carbon (DIC) is driven by the interplay of physical, chemical, and biological processes. Quantifying the spatiotemporal variability of these drivers is crucial for a mechanistic understanding of the ocean carbon sink and its future trajectory. Here, we use the Estimating the Circulation and Climate of the Ocean‐Darwin ocean biogeochemistry state estimate to generate a global‐ocean, data‐constrained DIC budget and investigate how spatial and seasonal‐to‐interannual variability in three‐dimensional circulation, air‐sea CO2 flux, and biological processes have modulated the ocean sink for 1995–2018. Our results demonstrate substantial compensation between budget terms, resulting in distinct upper‐ocean carbon regimes. For example, boundary current regions have strong contributions from vertical diffusion while equatorial regions exhibit compensation between upwelling and biological processes. When integrated across the full ocean depth, the 24‐year DIC mass increase of 64 Pg C (2.7 Pg C year−1) primarily tracks the anthropogenic CO2 growth rate, with biological processes providing a small contribution of 2% (1.4 Pg C). In the upper 100 m, which stores roughly 13% (8.1 Pg C) of the global increase, we find that circulation provides the largest DIC gain (6.3 Pg C year−1) and biological processes are the largest loss (8.6 Pg C year−1). Interannual variability is dominated by vertical advection in equatorial regions, with the 1997–1998 El Niño‐Southern Oscillation causing the largest year‐to‐year change in upper‐ocean DIC (2.1 Pg C). Our results provide a novel, data‐constrained framework for an improved mechanistic understanding of natural and anthropogenic perturbations to the ocean sink. Plain Language Summary The ocean has absorbed roughly 40% of fossil fuel carbon dioxide (CO2) emissions since the beginning of the industrial era. This so‐called “ocean carbon sink,” which primarily sequesters emissions in the form of dissolved inorganic carbon (DIC), plays a key role in regulating climate and mitigating global warming. However, we still lack a mechanistic understanding of how physical, chemical, and biological processes impact the ocean DIC reservoir in both space and time, and hence how the storage rates of emissions may change in the future. Here we use a global‐ocean biogeochemistry model Estimating the Circulation and Climate of the Ocean‐Darwin, which ingests both physical and biogeochemical observations to improve its accuracy, to map how ocean circulation, air‐sea CO2 exchange, and marine ecosystems have modulated the combined natural and anthropogenic ocean DIC budget for 1995–2018. We find that in the upper ocean, circulation provides the largest supply of DIC while biological processes drive the largest loss. Year‐to‐year changes in the ocean carbon sink are dominated by El Niño‐Southern Oscillation events in the equatorial Pacific Ocean, which then affect DIC globally. In summary, our data‐constrained, global‐ocean DIC budget constitutes a significant step forward toward understanding climate‐related changes to the ocean DIC reservoir. Key Points We evaluate the global dissolved inorganic carbon (DIC) budget for 1995–2018 using an ocean biogeochemistry state estimate Estimating the Circulation and Climate of the Ocean‐Darwin In the upper ocean, circulation provides the largest gain of DIC and biological processes are the dominant loss Interannual variability is greatest in equatorial regions and is associated with El Niño‐Southern Oscillation